The Application of Comic-Based Learning Assisted by Pixton to Improve Mathematical Creative Thinking Skill Of Class IX SMPN 8 Percut Sei Tuan - Elkana Indah Sari Pakpahan; Bornok Sinaga (Asian Journal of Applied Education (AJAE), 2023)
This research aims to improve creative thinking skills of students of SMPN 8 Percut Sei Tuan grade IX with material Congruence by using the The Application of Comic-Based Learning Assisted by Pixton to Improve Mathematical Creative Thinking Skill . The subject of this research is the students of class IX.3 of SMPN 8 Percut Sei Tuan in the academic year 2022/2023. The object of this research is students’ creative thinking skills by applying the Comic-Based Learning Assisted by Pixton and is assisted with to material Congruence in class IX.3 of SMPN 8 Percut Sei Tuan. This research used Classroom Action Research as the type of research, that consists two cycles, I and II. The instruments that used are observation, tests. The result analysis revealed that, the observation for mathematical creative thinking skill increased from 61% in cycle I to 83% in cycle II, there are 18 out of 30 students (60%) have attained the standard of mathematical creative thinking skills with mean score 68,06, improved after the execution in cycle II became 26 out of 30 students (87%) and mean 80, with gain index of 0,37 indicating a medium improvement. Therefore, the researcher concludes that applying of Comic-Based Learning Assisted by Pixton to Improve Mathematical Creative Thinking Skill Of Class IX SMPN 8 Percut Sei Tuan with material Congruence.